Development of tranquility perception scale: From tourists' perspective. (December 2021) - Hu, Meng; Lu, Youhai; Zhuang, Min; Zhang, Xiaowan; Zhang, Hui; Zhang, Yingying; Zhang, Jie; Liu, Peixue
Abstract: The pursuit of tranquility experience has emerged as a new demand in tourism, but the perception of tranquility in tourism remains understudied. Although there are tools in the psychology and acoustics to measure tranquility perception, they are not suitable in tourism research. Therefore, this paper attempts to explore two contextual tourists' perceptions scale of tranquility by analyzing two distinct destinations. Visual, auditory, and tactile involvement were introduced into the scale construction. A total of 1012 samples were collected from rural tranquil area and desert tranquil area. Following dimension construction and item production, EFA, CFA, reliability and validity tests were performed. Finally, a five-dimensional tranquility perception scale was developed. This study enriches the current themes and perspectives of multisensory involvement in the tranquility research and directs for further research on tourism, culture and tranquility experience.